Gamma-Aminobutyric Acid Modulation of Corticotrophin-Releasing Factor-41 Secretion from the Rat Hypothalamus in vitro. - Tsagarakis, S; Rees, L; Besser, G; Grossman, A (1990)
Abstract There is increasing evidence for a centrally mediated inhibitory effect of the amino-acid neurotransmitter y-aminobutyric acid (GABA) on the hypothalamo-pituitary-adrenal axis. In the present study, the direct effect of GABA in modulating the release of the 41-residue corticotrophin-releasing factor (CRF-41), the major CRF identified so far, was investigated in acute hypothalamic explants by utilizing previously validated incubation and assay techniques. While GABA (10(-7)'to 10(-5) M) had no effect on basal CRF-41 release (P > 0.05), it significantly suppressed K (-) (28 mM)-stimulated release in a dose-dependent manner (P < 0.01). A similar inhibitory effect was observed with the GABA agonist muscimol (10(-7) to 10(-5) M). Noradrenaline (10(-6) M) -induced CRF-41 release was also significantly inhibited by GABA 10(-6) M. The inhibitory effect of GABA on K(+)-stimulated CRF-41 secretion was completely. reversed by the GABA antagonists bicuculline and picrotoxin (10(-6) to 10(-5) M) in a dose-dependent fashion. Both bicuculline and picrotoxin stimulated basal and K(+) (28 mM)-stimulated CRF-41 release, indicating the presence of tonic inhibition by endogenous GABA in the basal state. Finally, GABA 10(-5) M was able to significantly inhibit the stimulated release of CRF-41 from the isolated median eminence. In summary, the present data provide strong evidence that GABA-induced inhibition of the hypothalamo-pituitary-adrenal axis is mediated, at least in part, through an inhibitory action on CRF-41 secretion. It is likely that these GABA receptors are located directly on CRF-41 neurons, probably on nerve terminals in the median eminence.